Genetic factors of thrombosis FII G20210A, FV G1691A (Arg506Gln) in patients with thoracoabdominal malignant tumors - A. A. Korolyova; S. S. Gerasimov; L. N. Lyubchenko (Успехи молекулярной онкологии, 2024)
Introduction. Malignant tumor is one of the leading factors of venous and arterial thrombosis. But there is no data on the need for a genetic testing protocol of cancer patients for genetic predisposition thrombotic conditions, despite the fact that a number of polymorphisms of hemostasis genes are considered to be unconditionally proven factors of high cumulative thrombogenic risk, and proteins encoded by these genes are direct links in the cascades of pathological hypercoagulation in neoplastic processes.Aim. To identify groups of high genetic risk of thrombotic complications among patients with malignant thoracoabdominal tumors.Materials and methods. The study included 223 patients with malignant tumors of the lung, stomach, esophagus, operated in the Department of Thoracic Oncology of the N.N. Blokhin National Research Center of Oncology in 2018–2019. The study groups consisted of patients with myocardial infarction (n = 62), ischemic stroke (n = 24), venous thrombosis/ venous thromboembolic complications (n = 40), patients without cardiovascular diseases, but with a family history burdened by cardiovascular diseases (n = 33). The control group included 81 patients.Results. Among patients with malignant tumors of thoracoabdominal localization, a statistically significant difference was determined in the frequency of carriage of the heterozygous genotype FV 1691GA (Arg506Gln) in patients who had a myocardial infarction (χ2 = 4.0; p = 0.046), who had venous thrombosis (χ2 = 4.118; p = 0.043), in the group of patients with burdened with a family history (χ2 = 4.997; p = 0.026) in comparison with the control group. Statistically significant difference in the frequency of carriage of the heterozygous variant of the mutation in the FII G20210A gene relative to the control group, it was determined in the group of patients who had an acute cerebrovascular accident (χ2 = 6.881; p = 0.009) and among patients with a burdened history (χ2 = 7.563; p = 0.006).Conclusion. In order to assess the risk of development and prevention of thrombotic complications in the perioperative period in patients with malignant thoracoabdominal tumors, who have suffered myocardial infarction, ischemic stroke, venous thrombosis/venous thromboembolic complications, as well as patients without cardiovascular pathology, but with thrombotic conditions in relatives of the first degree, it is advisable to perform DNA diagnostics at the prehospital stage to identify of gene polymorphisms FII G20210A and FV G1691A (Arg506Gln).